Aplikasi Manajemen Komplain Gedung Plaza Setiabudi Menggunakan Framework Ionic - Ade Galang Santika; Raditya Galih Whendasmoro; Iskandar Zulkarnain (FIKOM - Bung Karno University, 2022)
PT Jakarta Setiabudi Internasional Tbk manages an office building located in South Jakarta, namely the Plaza Setiabudi building, with a total area of ​​22,264 m2 that can be rented and while maintaining performance and improving service levels to maintain the loyalty of building tenants. In services to building tenants, there are complaints, so that several departments involved in handling tenant complaints include Facility Management, Tenant Relations, Engineering, House Keeping, Security, and Parking. complaints to find out the process, so that customers do not need to meet employees directly and the building tenant complaint management process can be completed, the building tenant compliance management application is designed using UML (Unified Modeling Lagunage) to help describe business processes and in making applications using the Java and C# programming languages and to optimize the database using the ionic framework.